Retinal Findings in COVID-19 Patient: A Literature Review - Tristira Urvina; Erwanda Fredy Purliawan (Puslitbang Sinergis Asa Professional, 2022)
Coronavirus disease 2019 (COVID-19) has been declared as worldwide pandemic. The most common symptoms are fever, fatigue, flu-like syndrome and accompanied by respiratory distress. About 10% of patients with COVID-19 in the acute phase show manifestations in the eye, especially in the retina. The activity of the cell surface enzyme protein angiotensin-converting enzyme 2 (ACE2) is believed underlying the clinical manifestations in the eye. This study aim to describe the clinical findings of COVID-19 in the retina which serves as a reference for diagnosis. The study was carried out using the PRISMA method with the keywords